Porous aluminum nitride microspheres and methods of making the same

CN123003295APending Publication Date: 2026-10-30HUNAN YAOHUA TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611070232.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]然而,现有球形氮化铝制备方法所生产的产物多为致密粉体,比表面积较低,内部孔结构不易控制

Benefits of technology

本发明以介孔密胺树脂球为前驱体经碳化制得介孔碳球,其高比表面积及残氮特性为铝离子提供了充足的负载位点与吸附性能。经表面改性引入含氧官能团,利用静电吸附进一步实现铝离子的高效负载。随后通过高温氮化,介孔孔道对铝进行原位限域,调控氮化铝纳米晶生长,获得多孔氮化铝碳复合微球。最后经脱碳去除模板,利用氮化铝纳米晶间的堆积间隙,保留微球形态,制得多孔氮化铝微球。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003295A_ABST
    Figure CN123003295A_ABST
Patent Text Reader

Abstract

The application provides a porous aluminum nitride microsphere and a preparation method thereof, and the preparation method comprises the following steps: a melamine resin sphere preparation step, a mesoporous carbon sphere preparation step, a surface modification step, a hierarchical immersion adsorption step, a high-temperature nitriding step and a decarburization step. The mesoporous carbon sphere containing nitrogen is prepared first, and then the surface of the mesoporous carbon sphere is modified, so that the oxygen-containing functional groups are formed on the mesoporous surface, and the oxygen-containing functional groups and nitrogen can promote the adsorption of aluminum ions, and finally the porous aluminum nitride microsphere is formed through high-temperature nitriding treatment. The method can realize the regulation of the microsphere form and the pore structure at the same time, so that the porous aluminum nitride microsphere in the microsphere form is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic materials technology, and in particular to a porous aluminum nitride microsphere and its preparation method. Background Technology

[0002] Aluminum nitride (AlN), as an advanced inorganic non-metallic material, has high thermal conductivity (theoretically up to 320 W·m). -1 ·K -1 Its comprehensive properties, including high resistivity, low dielectric constant, low coefficient of thermal expansion, and excellent chemical stability, have attracted widespread attention in fields such as electronic packaging, optoelectronic devices, and thermally conductive fillers.

[0003] Compared to ordinary aluminum nitride powder, porous aluminum nitride microspheres exhibit unique advantages in several cutting-edge application areas due to their high specific surface area, low density, high permeability, and unique pore confinement effect. In the field of thermal interface materials (TIMs), the porous structure provides mechanical interlocking anchors and storage margins for the polymer matrix, improving the interfacial bonding between the filler and the matrix and reducing interfacial thermal resistance. Simultaneously, the microsphere morphology endows the powder with good flowability and dispersibility, facilitating high filling rates in the matrix material and thus constructing a more efficient thermally conductive network. In the field of catalyst supports, the high specific surface area of ​​the porous structure provides abundant active sites and anchoring, which is beneficial for improving catalyst dispersibility and catalytic efficiency. In the field of phase change energy storage, porous aluminum nitride microspheres and their framework are ideal choices for constructing next-generation high-performance materials. Furthermore, theoretical studies have shown that porous aluminum nitride materials exhibit significant potential in solid-state hydrogen storage due to their moderate hydrogen adsorption energy and the absence of metal atom aggregation problems common in metal-modified carbon nanostructures.

[0004] However, existing methods for preparing spherical aluminum nitride mostly produce dense powders with low specific surface area and difficult-to-control internal pore structure. While spray granulation (e.g., CN202311836763.5) can obtain spherical powders, the resulting products have extremely low porosity after sintering. Furthermore, traditional carbothermal reduction methods often produce amorphous or irregular particles, making it difficult to directly obtain spherical microspheres. Although hydrothermal carbon sphere template methods (e.g., CN201910459958.X) can obtain hollow spherical morphologies, the hydrothermal carbon spheres used lack the ability to control the porous structure. Therefore, developing a method for preparing aluminum nitride microspheres that can simultaneously achieve control over both microsphere morphology and pore structure has significant scientific and practical value. Summary of the Invention

[0005] To address the problems existing in the prior art, the present invention aims to provide an aluminum nitride microsphere and its preparation method that can simultaneously achieve the control of microsphere morphology and pore structure.

[0006] A first aspect of the present invention provides a method for preparing porous aluminum nitride microspheres, comprising: Melamine resin ball preparation process: Prepare melamine resin balls with mesoporous structure; Mesoporous carbon sphere preparation process: Melamine resin spheres are carbonized to obtain mesoporous carbon spheres with a mesoporous structure; Surface modification process: The mesoporous carbon spheres are subjected to surface oxidation treatment to obtain surface-modified mesoporous carbon spheres; Graded impregnation and adsorption process: The surface-modified mesoporous carbon spheres are impregnated with aluminum salt solution to obtain mesoporous carbon spheres loaded with aluminum ions. High-temperature nitriding process: High-temperature nitriding treatment is performed on mesoporous carbon spheres loaded with aluminum ions to obtain porous aluminum-carbon nitrided composite microspheres; Decarburization process: The porous aluminum nitride carbon composite microspheres are decarburized to obtain porous aluminum nitride microspheres.

[0007] In some embodiments, the melamine resin ball preparation process includes: Emulsion preparation steps: Dissolve the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and 1,3,5-trimethylbenzene in water and stir to form a stable emulsion; Prepolymer solution preparation steps: Melamine, formaldehyde, alkali and water are mixed to form a melamine-formaldehyde prepolymer solution in a weakly alkaline environment; Mixed self-assembly step: The emulsion is added to the melamine-formaldehyde prepolymer solution and stirred, so that the emulsion and melamine-formaldehyde prepolymer self-assemble under weakly alkaline conditions to form a spherical micelle complex dispersion solution; Crosslinking and curing step: The pH of the spherical micelle composite dispersion solution is adjusted to weak acidity using acid to crosslink the melamine-formaldehyde prepolymer, resulting in a dispersion containing mesoporous melamine resin spheres. Post-processing steps: The dispersion containing mesoporous melamine resin balls is subjected to solid-liquid separation, washing, and drying to obtain mesoporous melamine resin balls.

[0008] In some embodiments, the preparation method further satisfies one or more of the following conditions: (1) Stable emulsion was obtained by vigorously stirring polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 1,3,5-trimethylbenzene and water for 4-8 hours; (2) The mass ratio of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer to 1,3,5-trimethylbenzene is preferably 1:0.5 to 1:5; (3) The alkali is at least one of ammonia, sodium hydroxide, and potassium hydroxide; (4) The pH of the weakly alkaline conditions is 8~10; (5) Stir at 80~120℃ for 0.5~2 hours to allow melamine and formaldehyde to react and form a melamine-formaldehyde prepolymer solution; (6) Add the emulsion to the melamine-formaldehyde prepolymer solution and stir for 1 to 3 hours to allow the emulsion to self-assemble with the melamine-formaldehyde prepolymer under weakly alkaline conditions to form a spherical micelle complex dispersion solution. (7) The pH of the weakly acidic environment is 2~5, the cross-linking and curing step is carried out under stirring, and the reaction time is 3~8 hours; (8) Drying is carried out at a temperature below 50°C.

[0009] In some embodiments, the carbonization temperature is 700~900°C; and / or, the mesoporous carbon spheres have channels radially distributed along their diameter.

[0010] In some embodiments, the surface oxidation treatment includes immersing mesoporous carbon spheres in a nitric acid solution with a concentration of 2-8 mol / L and refluxing them at 60-100°C for 4-12 hours to form oxygen-containing functional groups on their surface.

[0011] In some embodiments, the aluminum salt solution is one or more of aluminum nitrate aqueous solution, aluminum chloride aqueous solution, or aluminum sulfate aqueous solution; and / or, the aluminum ion concentration in the aluminum salt solution is 0.5~2 mol / L.

[0012] In some embodiments, the graded impregnation adsorption process includes at least two impregnation treatments, each of which involves dispersing surface-modified mesoporous carbon spheres in an aluminum salt solution with a pH of 6 to 8 and impregnating them for 6 to 24 hours.

[0013] In some embodiments, the preparation method also satisfies one or more of the following conditions: (1) Between two adjacent impregnation treatments, vacuum drying treatment is also performed on the mesoporous carbon balls after the previous impregnation treatment; (2) The graded impregnation adsorption process includes 3 to 5 impregnation stages, with the concentration of aluminum salts used in each stage increasing progressively. (3) The graded impregnation adsorption process also includes washing the mesoporous carbon balls obtained by the last impregnation process with polyethylene glycol solution, and vacuum drying the washed mesoporous carbon balls to obtain aluminum ion loaded mesoporous carbon balls.

[0014] In some embodiments, the high-temperature nitriding treatment temperature is 1400~1600°C; In some embodiments, the decarbonization process includes heating to 600-700°C at a heating rate of 2-10°C / min and holding at that temperature for 2-6 hours.

[0015] A second aspect of the present invention provides porous aluminum nitride microspheres, which are prepared by the above-described preparation method.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention uses mesoporous melamine resin spheres as a precursor to prepare mesoporous carbon spheres through carbonization. The high specific surface area and residual nitrogen characteristics of these carbon spheres provide ample loading sites and adsorption performance for aluminum ions. Surface modification introduces oxygen-containing functional groups, further enabling efficient loading of aluminum ions through electrostatic adsorption. Subsequently, high-temperature nitriding confines aluminum in situ within the mesoporous channels, controlling the growth of aluminum nitride nanocrystals to obtain porous aluminum nitride carbon composite microspheres. Finally, decarburization removes the template, utilizing the packing gaps between the aluminum nitride nanocrystals to preserve the microsphere morphology, thus producing porous aluminum nitride microspheres.

[0017] Other further beneficial effects of the present invention can be seen in the description of the specific embodiments. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0019] Figure 1 SEM images of the mesoporous carbon spheres prepared in Example 1 of the present invention are shown; Figure 2 The pore size distribution of the mesoporous carbon spheres prepared in Example 1 of the present invention is shown; Figure 3 SEM images of porous aluminum nitride microspheres prepared in Example 1 of the present invention are shown; Figure 4 The pore size distribution of the porous aluminum nitride microspheres prepared in Example 1 of the present invention is shown; Figure 5 The XRD pattern of the porous aluminum nitride microspheres prepared in Example 1 of the present invention is shown; Figure 6 SEM images of the aluminum nitride microspheres prepared in Comparative Example 1 of the present invention are shown. Figure 7 SEM images of the carbon spheres prepared in Comparative Example 2 of this invention are shown. Detailed Implementation

[0020] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0021] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0022] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0023] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, optionally sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0024] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" may also include or contain other components not listed, or may include only or contain the listed components.

[0025] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0026] In this article, in the semantic context of representing time, "h" represents hours.

[0027] As mentioned above, there is no method in the relevant technologies for preparing aluminum nitride microspheres with tunable microsphere morphology and pore structure.

[0028] A first aspect of the present invention provides porous aluminum nitride microspheres and a method for preparing the same, comprising: S100, melamine resin ball preparation process: Prepare melamine resin balls with mesoporous structure; S200, Mesoporous Carbon Sphere Preparation Process: Melamine resin spheres are carbonized to obtain mesoporous carbon spheres with a mesoporous structure; S300, Surface modification process: The mesoporous carbon spheres are subjected to surface oxidation treatment to obtain surface-modified mesoporous carbon spheres; S400, graded impregnation and adsorption process: surface-modified mesoporous carbon spheres are impregnated with aluminum salt solution to obtain mesoporous carbon spheres loaded with aluminum ions. S500, High-temperature nitriding process: High-temperature nitriding treatment is performed on mesoporous carbon spheres loaded with aluminum ions to obtain porous aluminum-carbon nitrided composite microspheres; S600, Decarburization process: The porous aluminum nitride carbon composite microspheres are decarburized to obtain porous aluminum nitride microspheres.

[0029] In this embodiment of the invention, melamine resin spheres with a mesoporous structure are first prepared, and then the melamine resin spheres are carbonized to obtain mesoporous carbon spheres. Mesoporous carbon spheres provide abundant pores and a high specific surface area, providing ample space for loading aluminum ions. The residual nitrogen element in the mesoporous carbon spheres prepared from melamine resin can improve the adsorption performance of aluminum ions. Surface modification of the mesoporous carbon spheres can introduce oxygen-containing functional groups such as carboxyl groups on the surface of the carbon spheres and the surface layer of the pores, further achieving efficient adsorption of aluminum ions through electrostatic adsorption under weakly acidic conditions, resulting in aluminum-loaded mesoporous carbon spheres. High-temperature nitriding treatment of the aluminum-loaded mesoporous carbon spheres ensures the uniform distribution of aluminum ions within the pores of the mesoporous carbon spheres. During high-temperature nitriding, the aluminum ions are confined in situ by the mesoporous pores, and the size of the aluminum nitride nanocrystals is constrained by the pore size, achieving controllable growth of aluminum nitride nanocrystals, resulting in porous aluminum nitride carbon composite microspheres. The porous aluminum nitride carbon composite microspheres were decarburized to remove the carbon template. The aluminum nitride nanocrystals retained the microsphere morphology, and due to the stacking gaps between the aluminum nitride nanocrystals, porous aluminum nitride microspheres were finally formed.

[0030] In this embodiment, the S100 melamine resin ball preparation process can prepare melamine resin balls with a mesoporous structure, which can be used as a precursor for preparing mesoporous carbon balls.

[0031] In some embodiments, the S100 melamine resin ball preparation process includes: S110, Emulsion preparation steps: Dissolve the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and 1,3,5-trimethylbenzene in water and stir to form a stable emulsion; S120, Prepolymer Solution Preparation Steps: Melamine, formaldehyde, alkali and water are mixed to form a melamine-formaldehyde prepolymer solution in a weakly alkaline environment; S130, Mixed self-assembly step: Add the emulsion to the prepolymer solution and stir to allow the emulsion to self-assemble with the melamine-formaldehyde prepolymer under weakly alkaline conditions to form a spherical micelle complex dispersion solution; S140, Crosslinking and Curing Step: The pH of the spherical micelle composite dispersion solution is adjusted to weak acidity using acid to crosslink the melamine-formaldehyde prepolymer, resulting in a dispersion containing mesoporous melamine resin spheres. S150, Post-processing steps: The dispersion containing mesoporous melamine resin balls is subjected to solid-liquid separation, washing, and drying to obtain mesoporous melamine resin balls.

[0032] In the S110 emulsion preparation step, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (F127) is used as a template agent and 1,3,5-trimethylbenzene (TMB) is used as a pore expander, both mixed in water. F127 is an amphiphilic polymer, with the hydrophobic polyoxyethylene segments dissolving in water with the hydrophobic polyoxypropylene segments coheding to form a hydrophobic core. The oily 1,3,5-trimethylbenzene is coated in the hydrophobic core, thereby forming polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer-1,3,5-trimethylbenzene swelling micelles (F127-TMB micelles). Under stirring conditions, a stable emulsion is obtained.

[0033] In some embodiments, a stable emulsion is obtained by vigorously stirring a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 1,3,5-trimethylbenzene, and water for 4-8 hours. Exemplary stirring times are 4 hours, 5 hours, 6 hours, 7 hours, and 8 hours. The stirring time and rate can also be appropriately adjusted according to the needs of those skilled in the art.

[0034] In some embodiments, the mass ratio of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer to 1,3,5-trimethylbenzene is preferably 1:0.5 to 1:5. Adjusting the mass ratio of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer to 1,3,5-trimethylbenzene can adjust the swelling degree of F127-TMB micelles, thereby adjusting the pore size of the mesoporous melamine resin spheres. As the 1,3,5-trimethylbenzene content increases, the pore size of the mesoporous melamine resin spheres increases. Excessively high 1,3,5-trimethylbenzene content will damage the morphology of the mesoporous melamine resin spheres, reduce uniformity, and introduce surface defects. Insufficient 1,3,5-trimethylbenzene content will result in a weak pore-expanding effect, with insufficient pore number and size.

[0035] In the preparation step of S120 prepolymer solution, melamine, formaldehyde, alkali and water are mixed. Melamine and formaldehyde preferentially undergo hydroxymethyl addition in a weakly alkaline environment, resulting in low intermolecular condensation. The product is mainly small molecule polyhydroxymethyl melamine, which can be stably dissolved in water to form melamine-formaldehyde prepolymer solution.

[0036] In the above embodiments, the alkali can be at least one of ammonia, sodium hydroxide, and potassium hydroxide. It should be noted that, to avoid localized over-alkaliness, it is preferable to first dissolve strong alkalis such as sodium hydroxide or potassium hydroxide in some water to form an aqueous solution before mixing it with the remaining components. More preferably, ammonia is used as the alkali to adjust the pH to a weakly alkaline state. Ammonia adjustment avoids the introduction of metal ions such as potassium and sodium, thus preventing the introduction of potassium and sodium ions during the subsequent preparation of aluminum nitride and thus avoiding any impact on the purity of the aluminum nitride.

[0037] In some embodiments, the pH of the weakly alkaline conditions is 8-10. Too high a pH may cause dehydration condensation between hydroxymethyl groups to form methylene bridges, resulting in a rapid increase in molecular weight and causing the resin to emulsify, precipitate, or gel. Too low a pH may cause rapid polycondensation of melamine and formaldehyde.

[0038] In some embodiments, the mixture is stirred at 80-120°C for 0.5-2 hours to allow melamine and formaldehyde to react and form a melamine-formaldehyde prepolymer solution.

[0039] In the S130 mixing and self-assembly step, the emulsion is added to the melamine-formaldehyde prepolymer solution and stirred, allowing the melamine-formaldehyde prepolymer to adsorb onto the hydrophilic segments on the surface of the emulsion. The F127-TMB micelles, which have adsorbed a large amount of melamine-formaldehyde prepolymer, are uniformly dispersed in the aqueous phase and undergo synergistic self-assembly, initially aggregating to form spherical micelle aggregates. At this point, the melamine-formaldehyde prepolymer has not yet polymerized and remains a water-soluble small-molecule prepolymer.

[0040] In some embodiments, the emulsion is added to a melamine-formaldehyde prepolymer solution and stirred for 1 to 3 hours, so that the emulsion self-assembles with the melamine-formaldehyde prepolymer under weakly alkaline conditions to form a spherical micelle complex dispersion solution.

[0041] In the S140 crosslinking and curing step, the pH of the dispersion solution of the spherical micelle complex is adjusted to a weakly acidic state by using acid, so that the melamine-formaldehyde prepolymer in the micelle complex is crosslinked. As the degree of crosslinking increases, the small molecule melamine-formaldehyde prepolymer gradually crosslinks into a three-dimensional water-insoluble melamine resin polymer framework, which precipitates out from the aqueous phase to form mesoporous melamine resin spheres.

[0042] In some embodiments, the pH of the weakly acidic environment is 2-5. In further embodiments, the crosslinking and curing step is carried out under stirring conditions for a reaction time of 3-8 hours.

[0043] In the S150 post-processing step, mesoporous melamine resin balls are separated from the dispersion through solid-liquid separation. The method of solid-liquid separation is not particularly limited here; conventional methods such as vacuum filtration and centrifugation can be used. The separated mesoporous melamine resin balls are washed with a solvent to remove unreacted monomers and oligomers, and then dried to obtain dried mesoporous melamine resin balls.

[0044] It should be noted that the above drying is preferably carried out at a relatively low temperature, for example, below 50°C. In some examples, the drying temperature is 40°C and the drying time is 8-10 hours.

[0045] In this embodiment, the S200 mesoporous carbon sphere preparation process mainly utilizes high temperature to carbonize melamine resin spheres. During the reaction, small molecule water is gradually removed, F127 and TMB template undergo thermal decomposition and volatilization, triazine ring deamination and fused ring aromatization, carbon network graphitization, and thermal rearrangement of nitrogen-containing functional groups, accompanied by the escape of gases such as H2O, CO, CO2, NH3, and N2. Due to the high thermal stability of the triazine ring structure of melamine resin, a large number of nitrogen atoms are retained by embedding in the carbon skeleton in the form of pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen, resulting in in-situ nitrogen-doped mesoporous carbon spheres. These mesoporous carbon spheres inherit the spherical morphology and mesoporous structure of melamine resin spheres, possessing abundant pores and a high specific surface area. Furthermore, due to the intrinsic properties of melamine resin, a high nitrogen doping content is retained in the carbon sphere skeleton after carbonization, which is beneficial for the subsequent adsorption of aluminum ions.

[0046] In some embodiments, the carbonization temperature is 700~900°C. In some examples, the carbonization process includes heating to 700~900°C at a heating rate of 0.5~5°C / min and holding at this temperature for 2~6 hours.

[0047] In some embodiments, the mesoporous carbon spheres have channels radially distributed along their diameter. The radial distribution of channels along the diameter facilitates the entry of aluminum ions into the channels, thereby increasing the aluminum ion loading.

[0048] In this embodiment, the S300 surface modification process performs surface oxidation treatment on the mesoporous carbon spheres, forming oxygen-containing functional groups on the pore surface of the mesoporous carbon spheres, which further significantly enhances the adsorption capacity of aluminum ions, allowing sufficient aluminum ions to be loaded onto the mesoporous carbon spheres, thus providing aluminum raw materials for subsequent high-temperature nitriding treatment.

[0049] It should be noted that the purpose of surface modification is to form groups on the mesoporous carbon spheres that can interact with aluminum ions. The raw materials for surface modification are not particularly limited here; they can be a mixture of nitric acid and sulfuric acid, a mixture of sulfuric acid and hydrogen peroxide, or other components.

[0050] In some examples, the surface modification treatment involves immersing mesoporous carbon spheres in a nitric acid solution with a concentration of 2–8 mol / L and refluxing them at 60–100 °C for 4–12 hours to form oxygen-containing functional groups on their surface.

[0051] Understandably, after the above treatment, the surface-modified mesoporous carbon spheres can be cooled to room temperature, washed with deionized water until neutral, and dried to facilitate subsequent graded impregnation and adsorption processes.

[0052] In this embodiment, the S400 graded impregnation and adsorption process uses an aluminum salt solution to impregnate the surface-modified mesoporous carbon spheres, allowing aluminum ions to enter the pores of the mesoporous carbon spheres. The aluminum ions interact with the oxygen-containing functional groups and N in the surface-modified mesoporous carbon spheres and are adsorbed onto the surface of the pores, resulting in mesoporous carbon spheres loaded with aluminum ions.

[0053] It is understood that the aluminum salt solution primarily provides aluminum ions. Optionally, the aluminum salt solution is one or more of aluminum nitrate aqueous solution, aluminum chloride aqueous solution, or aluminum sulfate aqueous solution. Optionally, the aluminum ion concentration in the aluminum salt solution is 0.5~2 mol / L.

[0054] In some embodiments, the S400 graded impregnation adsorption process includes at least two impregnation treatments, each of which involves dispersing surface-modified mesoporous carbon spheres in an aluminum salt solution with a pH of 6-8 and impregnating them for 6-24 hours. An aluminum salt solution with a suitable pH helps to prevent the hydrolysis of aluminum ions and promotes the entry of aluminum ions into the pores of the mesoporous carbon spheres.

[0055] In some embodiments, between two adjacent impregnation processes, a vacuum drying process is further included on the mesoporous carbon spheres after the previous impregnation process. After the vacuum drying process on the mesoporous carbon spheres after the previous impregnation process, the next impregnation process is performed. The drying process allows the solvent of the aluminum ion solution filling the pores of the mesoporous carbon spheres to evaporate, aluminum ions to be adsorbed into the pores, and the pores to reopen, thereby facilitating the re-entry of the aluminum salt solution into the pores during the next impregnation process. This increases the aluminum ion loading in the mesoporous carbon spheres. For example, the vacuum drying conditions are vacuum drying at 80°C for 6-8 hours.

[0056] In some embodiments, the S400 graded impregnation adsorption process includes 3 to 5 impregnation stages, with the concentration of aluminum salt used in each impregnation stage increasing progressively.

[0057] In some embodiments, the S400 staged impregnation and adsorption process further includes rinsing the mesoporous carbon spheres obtained from the final impregnation treatment with a polyethylene glycol solution, and then vacuum drying the rinsed mesoporous carbon spheres to obtain aluminum ion-loaded mesoporous carbon spheres. For example, a distilled aqueous solution containing 4-10 wt% polyethylene glycol 400 (PEG400) is used for rinsing. For example, the drying conditions are: vacuum drying at 80°C for 6-8 hours. The product is then subjected to the next stage of impregnation, and after the final stage of impregnation, the product is rinsed once with distilled water containing 4-10 wt% polyethylene glycol 400, and finally vacuum dried to obtain saturated aluminum ion-loaded mesoporous carbon spheres. Rinsing the mesoporous carbon spheres obtained from the final impregnation treatment with a polyethylene glycol solution can form a polyethylene glycol coating layer on the surface of the mesoporous carbon spheres. The polyethylene glycol coating layer is beneficial for promoting the dispersion of porous aluminum nitride microspheres during the subsequent high-temperature nitriding process.

[0058] In this embodiment, the S500 high-temperature nitriding process, conducted in a nitrogen-containing atmosphere, causes the aluminum ions in the aluminum-loaded mesoporous carbon spheres to undergo a carbothermic reduction nitriding reaction with carbon. The in-situ generated aluminum nitride is simultaneously supported and guided by the mesoporous carbon sphere framework, ultimately resulting in porous aluminum nitride carbon composite microspheres. It is understood that the nitrogen-containing atmosphere can be nitrogen or ammonia.

[0059] In some embodiments, the temperature for high-temperature nitriding is 1400~1600°C. For example, the high-temperature nitriding process includes: heating to 1400~1600°C at a heating rate of 1~10°C / min, and holding at that temperature for 4~8 hours.

[0060] In this embodiment, the S600 decarburization process decarburizes the porous aluminum nitride carbon composite microspheres under an oxygen-containing atmosphere, causing the carbon in the porous aluminum nitride carbon composite microspheres to be oxidized and removed, while the aluminum nitride component is retained, thereby obtaining porous aluminum nitride microspheres.

[0061] In some embodiments, the decarbonization process includes: heating to 600-700°C at a heating rate of 2-10°C / min and holding at that temperature for 2-6 hours.

[0062] A second aspect of the present invention provides a porous aluminum nitride microsphere, which is prepared by the above method.

[0063] In some embodiments, the porous aluminum nitride microspheres have a particle size D50 of 50~1000 nm and a specific surface area of ​​50~500 m² / g.

[0064] The following embodiments describe the disclosure of this application in more detail. These embodiments are for illustrative purposes only, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all reagents and raw materials used in the embodiments are commercially available or synthesized by conventional methods, and the instruments used in the embodiments are also commercially available.

[0065] In the following embodiments, the microstructure was characterized using a field emission scanning electron microscope (SEM) of the German Zeiss GM500 FESEM (model). In the following embodiments, the pore size and specific surface area were characterized using the BET method (Micromeritics ASAP2460). In the following embodiments, a laser particle size analyzer (OMEC LS-POP(9)) was used to characterize the particle size distribution; In the following embodiments, the XRD characteristics were characterized using a German Bruker D4 X-ray diffractometer.

[0066] Example 1 Melamine resin ball preparation process Emulsion preparation steps: Dissolve 1.0 g F127 in 100 mL of deionized water, add 1.5 g TMB, and stir vigorously for 6 hours to form a stable F127 / TMB emulsion.

[0067] Prepolymer solution preparation steps: Add 1.26 g melamine, 2.0 mL 37% formaldehyde solution and 0.05 mL ammonia water to 40 mL deionized water, stir at 100℃ for 0.5 hours until the solution is homogeneous and transparent to form melamine formaldehyde prepolymer (MF prepolymer) solution.

[0068] Mixed self-assembly step: Add F127 / TMB emulsion to melamine formaldehyde prepolymer solution and stir for 2 hours to stabilize TMB / F127 emulsion droplets under weakly alkaline conditions and allow for self-assembly with MF.

[0069] Crosslinking and curing step: Then add 2 mL of acetic acid (adjust pH to about 3.5) and continue stirring for 6 hours to promote the crosslinking and polymerization of MF prepolymer and at the same time promote micelle self-assembly to form mesoporous melamine resin balls with a mesoporous structure.

[0070] Post-processing steps: After the reaction was completed, the solution turned bright milky white. The product was collected by centrifugation (8000 rpm, 10 minutes), washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 40°C for 8 hours to obtain mesoporous melamine resin balls.

[0071] Mesoporous carbon sphere preparation process Mesoporous melamine resin spheres were placed in a tube furnace and heated to 800°C at a heating rate of 2°C / min under a nitrogen atmosphere. The temperature was held for 4 hours, and then allowed to cool naturally to room temperature to obtain mesoporous carbon spheres. The morphology and particle size distribution of the mesoporous carbon spheres are shown in the reference. Figure 1 , Figure 2 .

[0072] Surface modification process 1.0 g of mesoporous carbon spheres were immersed in 50 mL of 6 mol / L nitric acid solution and refluxed at 80 °C for 8 hours. After treatment, the mixture was allowed to cool naturally, washed with deionized water until the pH of the washing solution was approximately 7, and dried at 80 °C for 10 hours to obtain surface-modified mesoporous carbon spheres.

[0073] Graded impregnation and adsorption process 0.5 g of surface-modified mesoporous carbon spheres were dispersed in 50 mL of 1.0 mol / L aluminum nitrate aqueous solution, and the pH was adjusted to approximately 4 with dilute nitric acid. The mixture was stirred and impregnated at room temperature for 12 hours. After impregnation, the mixture was centrifuged, washed twice with deionized water, and vacuum dried at 80 °C for 10 hours. The product was then subjected to staged impregnation and adsorption in 1.5 mol / L and 2.0 mol / L aluminum nitrate aqueous solutions using a similar procedure. After the final stage of impregnation and adsorption, the product was rinsed once with a distilled aqueous solution containing 8 wt% polyethylene glycol 400. Finally, the product was vacuum dried to obtain saturated aluminum-loaded mesoporous carbon spheres.

[0074] High-temperature nitriding process Mesoporous carbon spheres loaded with aluminum ions were placed in a tube furnace and heated to 1500℃ at a heating rate of 5℃ / min under a nitrogen atmosphere (flow rate 100 mL / min). The temperature was held for 6 hours and then naturally cooled to room temperature to obtain aluminum nitride carbon composite microspheres.

[0075] Decarbonization process Aluminum nitride carbon composite microspheres were placed in a muffle furnace and heated to 650°C at a heating rate of 5°C / min in air atmosphere. The temperature was held for 4 hours and then naturally cooled to room temperature to obtain white powdered aluminum nitride microspheres.

[0076] Product characterization: The aluminum nitride microspheres obtained in this example were found to be spherical with a particle size D50 of 310 nm. Figure 3 The specific surface area is 136 m² / g. Figure 4 The XRD pattern shows a pure aluminum nitride phase. Figure 5 .

[0077] Example 2 The basic steps are the same as in Example 1, except that the particle size is controlled by adjusting the ratio of F127 to TMB and the reaction conditions in step (1): The dosage of F127 was changed to 0.6 g, the dosage of TMB was changed to 0.8 g, and the other steps were the same as in Example 1.

[0078] The resulting aluminum nitride microspheres had a particle size D50 of 220 nm and a specific surface area of ​​approximately 55 m² / g.

[0079] Comparative Example 1 The basic steps are the same as in Example 1, except that: The aluminum salt solution was replaced with an aluminum chloride aqueous solution; the nitriding temperature was adjusted to 1700℃ and held for 6 hours.

[0080] The resulting aluminum nitride microspheres exhibited severe adhesion and aggregation. Due to the increased temperature and prolonged holding time, the porous structure of the microspheres collapsed. Figure 6 ).

[0081] Comparative Example 2 The basic steps are the same as in Example 1, except that F127 / TMB emulsion is not prepared and added. Other steps are similar to those in Example 1.

[0082] The resulting carbon spheres exhibited poor uniformity in particle size distribution, with a D50 of 480 nm. The particles had rough surfaces and lacked mesoporous structures, failing to meet the requirements for effective aluminum ion loading and thus preventing the acquisition of aluminum nitride products. (See [link to article]). Figure 7 .

[0083] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0084] The embodiments described above are merely illustrative of several implementations of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A method for preparing porous aluminum nitride microspheres, characterized in that, include: Melamine resin ball preparation process: Prepare melamine resin balls with mesoporous structure; Mesoporous carbon sphere preparation process: The melamine resin spheres are subjected to carbonization treatment to obtain mesoporous carbon spheres with a mesoporous structure; Surface modification process: The mesoporous carbon spheres are subjected to surface oxidation treatment to obtain surface-modified mesoporous carbon spheres; Graded impregnation and adsorption process: The surface-modified mesoporous carbon spheres are impregnated with aluminum salt solution to obtain mesoporous carbon spheres loaded with aluminum ions; High-temperature nitriding process: The mesoporous carbon spheres loaded with aluminum ions are subjected to high-temperature nitriding treatment to obtain porous aluminum-carbon nitrided composite microspheres; Decarburization process: The porous aluminum nitride carbon composite microspheres are subjected to decarburization treatment to obtain porous aluminum nitride microspheres.

2. The method for preparing porous aluminum nitride microspheres according to claim 1, characterized in that, The melamine resin ball preparation process includes: Emulsion preparation steps: Dissolve the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and 1,3,5-trimethylbenzene in water and stir to form a stable emulsion; Prepolymer solution preparation steps: Melamine, formaldehyde, alkali and water are mixed to form a melamine-formaldehyde prepolymer solution in a weakly alkaline environment; Mixed self-assembly step: The emulsion is added to the melamine-formaldehyde prepolymer solution and stirred, so that the emulsion and the melamine-formaldehyde prepolymer self-assemble under weakly alkaline conditions to form a spherical micelle complex dispersion solution; Crosslinking and curing step: The pH of the spherical micelle composite dispersion solution is adjusted to weak acidity using acid to crosslink the melamine-formaldehyde prepolymer, resulting in a dispersion containing mesoporous melamine resin spheres. Post-processing steps: The dispersion containing mesoporous melamine resin balls is subjected to solid-liquid separation, washing, and drying to obtain mesoporous melamine resin balls.

3. The method for preparing porous aluminum nitride microspheres according to claim 2, characterized in that, The preparation method also satisfies one or more of the following conditions: (1) Stable emulsion was obtained by vigorously stirring polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, 1,3,5-trimethylbenzene and water for 4-8 hours; (2) The mass ratio of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer to the 1,3,5-trimethylbenzene is preferably 1:0.5 to 1:5; (3) The alkali is at least one of ammonia, sodium hydroxide, and potassium hydroxide; (4) The pH of the weakly alkaline conditions is 8~10; (5) Stir at 80~120℃ for 0.5~2 hours to allow the melamine and formaldehyde to react and form a melamine-formaldehyde prepolymer solution; (6) Add the emulsion to the melamine-formaldehyde prepolymer solution and stir for 1 to 3 hours to allow the emulsion to self-assemble with the melamine-formaldehyde prepolymer under weakly alkaline conditions to form the spherical micelle composite dispersion solution; (7) The pH of the weakly acidic environment is 2 to 5, and the cross-linking curing step is carried out under stirring, with a reaction time of 3 to 8 hours; (8) The drying is carried out at a temperature below 50°C.

4. The method for preparing porous aluminum nitride microspheres according to claim 1, characterized in that, The carbonization treatment temperature is 700~900℃; and / or, The mesoporous carbon spheres have channels radially distributed along their diameter.

5. The method for preparing porous aluminum nitride microspheres according to claim 1, characterized in that, The surface oxidation treatment includes immersing the mesoporous carbon spheres in a nitric acid solution with a concentration of 2-8 mol / L and refluxing them at 60-100°C for 4-12 hours to form oxygen-containing functional groups on their surface.

6. The method for preparing porous aluminum nitride microspheres according to claim 1, characterized in that, The aluminum salt solution is one or more of aluminum nitrate aqueous solution, aluminum chloride aqueous solution, or aluminum sulfate aqueous solution; and / or, The aluminum ion concentration in the aluminum salt solution is 0.5~2 mol / L.

7. The method for preparing porous aluminum nitride microspheres according to claim 1, characterized in that, The graded impregnation and adsorption process includes at least two impregnation treatments, each of which involves dispersing surface-modified mesoporous carbon spheres in an aluminum salt solution with a pH of 6 to 8 and impregnating them for 6 to 24 hours.

8. The method for preparing porous aluminum nitride microspheres according to claim 7, characterized in that, The preparation method also satisfies one or more of the following conditions: (1) Between two adjacent impregnation treatments, a vacuum drying treatment is also performed on the mesoporous carbon balls after the previous impregnation treatment; (2) The graded impregnation and adsorption process includes 3 to 5 impregnation stages, with the concentration of aluminum salt used in each impregnation stage increasing progressively; (3) The graded impregnation and adsorption process further includes washing the mesoporous carbon balls obtained by the last impregnation process with polyethylene glycol solution, and vacuum drying the washed mesoporous carbon balls to obtain aluminum ion-loaded mesoporous carbon balls.

9. The method for preparing porous aluminum nitride microspheres according to claim 1, characterized in that, The high-temperature nitriding treatment is performed at a temperature of 1400~1600℃; and / or, The decarbonization process includes: heating to 600-700℃ at a heating rate of 2-10℃ / min and holding at that temperature for 2-6 hours.

10. A porous aluminum nitride microsphere, characterized in that, The porous aluminum nitride microspheres are prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of hollow spherical aluminium nitride powder material and aluminium nitride porous ceramic

    CN110194441A

  • Densified spherical aluminum nitride as well as preparation method and application thereof

    CN118185344A